2022
DOI: 10.2991/assehr.k.220204.065
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Local Government Tanah Karo Regency in Responding to Mount Sinabung Eruption in Indonesia

Abstract: Local governments have an important role in minimizing disaster risk. This is related to development goals in the region. Therefore, local governments must have the capacity to guide the community in order to minimize disaster risk. This aspect is contained in the context of this paper, namely knowing the capacity of the Tanah Karo Regency Government in minimizing the risk of the eruption of Mount Sinabung. In minimizing disaster risk, the Tanah Karo Regency Government has established the Regional Disaster Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As mentioned in the introduction, Mount Sinabung suddenly reactivated and released volcanic ashes in 2010 (BBC News, 2010). But several studies conducted 7-11 years after the eruption showed that the existing efforts and programs to reduce disaster risk is still needed to be fixed or improved (Situmorang, 2018;Wulandari et al, 2018;Sihombing et al, 2022). The existing studies on Mount Sinabung were conducted at the community and local government levels (Situmorang, 2018;Wulandari et al, 2018;Erianjoni et al, 2020;Sihombing et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned in the introduction, Mount Sinabung suddenly reactivated and released volcanic ashes in 2010 (BBC News, 2010). But several studies conducted 7-11 years after the eruption showed that the existing efforts and programs to reduce disaster risk is still needed to be fixed or improved (Situmorang, 2018;Wulandari et al, 2018;Sihombing et al, 2022). The existing studies on Mount Sinabung were conducted at the community and local government levels (Situmorang, 2018;Wulandari et al, 2018;Erianjoni et al, 2020;Sihombing et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…But several studies conducted 7-11 years after the eruption showed that the existing efforts and programs to reduce disaster risk is still needed to be fixed or improved (Situmorang, 2018;Wulandari et al, 2018;Sihombing et al, 2022). The existing studies on Mount Sinabung were conducted at the community and local government levels (Situmorang, 2018;Wulandari et al, 2018;Erianjoni et al, 2020;Sihombing et al, 2022). There is no research that could explain the situation in the school community that is considered the vulnerable part and the central point in the community (Takahashi et al, 2015;Amri et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations